Gutmaro GÓMEZ BRAVO y Jorge MARCO, La obra del miedo. Violencia y sociedad en la España franquista (1936-1950), Barcelona, Península, 2011 - del Arco Blanco, Miguel Ángel (Historia del Presente, 2012)
-